BREAKING BARRIERS: HOW ACCESS TO EDUCATION TRANSFORMS THE LIVES OF WOMEN IN AFGHANISTAN - Bashardost, Meena; Esmati, Ramina; Khodayar, Farkhunda; Hussaini, Nazanin; Quraishi, Tamanna (Yayasan Education and Social Center, 2025)
Education is a vital instrument for empowering women, particularly in developing countries like Afghanistan, where social, economic, and cultural barriers often restrict access to quality education. Despite global efforts to enhance gender equality, Afghan women face persistent challenges that hinder their educational advancement. This study aims to explore how access to education influences the social and economic empowerment of Afghan women, identify the primary challenges limiting their educational opportunities, and examine the effectiveness of digital education platforms in expanding access for women in restrictive or remote areas. A quantitative survey was conducted with 120 female participants from diverse academic backgrounds—medical, economics, and computer science faculties in Afghanistan. Participants responded to a series of questions using a 5-point Likert scale, assessing perceptions related to empowerment, barriers, and digital learning. The data were analyzed using descriptive statistics to determine prevalent trends and attitudes. Findings indicate that most participants agree that education significantly enhances social and economic empowerment for women. Financial difficulties, poverty, and cultural norms were identified as major barriers to accessing quality education. Additionally, digital education platforms were seen as moderately to highly effective in reaching women in remote or conservative regions, with many participants expressing comfort and willingness to engage with online learning tools. Education remains a critical pathway to women’s empowerment in Afghanistan. Addressing financial and cultural obstacles, alongside expanding digital education initiatives, is essential to promote equitable access and enable Afghan women to overcome traditional barriers. Policymakers should prioritize these areas to facilitate inclusive educational development